2019
DOI: 10.1096/fj.201802433r
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor regulates innate γδ T‐cell responsesviaIL‐17 expression

Abstract: T cells expressing invariant γδ antigen receptors (γδ T cells) bridge innate and adaptive immunity and facilitate barrier responses to pathogens. Macrophage migration inhibitory factor (MIF) is an upstream mediator of host defense that up‐regulates the expression of pattern recognition receptors and sustains inflammatory responses by inhibiting activation‐induced apoptosis in monocytes and macrophages. Surprisingly, Mif−/− γδ T cells, when compared with wild type, were observed to produce >10‐fold higher level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…also reported that MIF neutralizing antibodies inhibited the proliferation of mouse splenocytes induced by the toxic-shock syndrome toxin 1 (TSST1) and protected mice from TSST1-induced shock 31 . However, apparently contradictory observations have just been reported 32 . Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…also reported that MIF neutralizing antibodies inhibited the proliferation of mouse splenocytes induced by the toxic-shock syndrome toxin 1 (TSST1) and protected mice from TSST1-induced shock 31 . However, apparently contradictory observations have just been reported 32 . Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no reports of MIF driving gd T cell effector functions in the context of tumorigenesis, MIF has been shown to regulate gd T cell expression of IL-17 following stimulation with IL-1b and IL-23 in a mouse model of Gram-positive toxic shock syndrome (162). Interestingly, addition of recombinant MIF to lymph node-derived cells directly increases IL-17 production further supporting an amplification role for MIF in the regulation of gd T17 cell-expressed IL-17 (163).…”
Section: Gamma Delta T Cells (Gd T)mentioning
confidence: 99%
“…AM is the majority part of alveolar and the macrophage is classical organ damage restorer. The activated macrophage is the main source of IL-17 [20]. Plasticity is the characteristics of macrophages.…”
Section: Discussionmentioning
confidence: 99%